From Strategy to Fluency: EFL Learners’ Preferences for Cognitive Learning Strategies to Overcome Psychological and Linguistic Challenges in Speaking - Agustina, Rahmawati; Dio Resta Permana; Dita Rizki Anggraini (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan UIN Saizu Purwokerto, 2025)
English as an international language has a crucial role, especially focusing on speaking skill among EFL learner. Many Indonesian students face difficulties in speaking English due to linguistic challenges (vocabulary, grammar, pronunciation) and non-linguistic factors (anxiety, low motivation, lack of confidence). The 2024 English Proficiency Index places Indonesia in the